Preparation of Regional Regulations in the Context of Implementing the Content of Presidential Regulation Number 38 of 2015 concerning Cooperation Agreements between Government and Business Entities in the Provision of Infrastructure - Kurdi; Cut Zulfahnur Syafitri; Prita Amalia; Wardhana, Yuki M.A (Journal of Law, Politic and Humanities, 2024)
Government cooperation with business entities (PPP) provides many benefits in infrastructure development. however, the content material of the existing PPP legal basis is not suitable for implementation in the regions due to differences in budget availability. in connection with this, it is necessary to implement the content material of the presidential regulation in the form of regional regulations. this research uses a type of normative juridical research conducted by examining various previously available sources. in connection with this, in order to facilitate the analysis of legal sources, the author also uses statutory and conceptual approaches in this research. The result of this research is that presidential regulation number 38 of 2015 which discusses PPP has covered various matters like a law and actually the local government has a clear legal basis in order to pour the content material contained in the presidential regulation which the legal basis is contained in the basic law, the law even in the presidential regulation which discusses PPP itself so that the local government should be able to pour the material of the presidential regulation in the form of regional regulations.